The Effectiveness of Using Toontastic-Based Animated Learning Media on Students' Interest In Learning Indonesian Language Indonesia Students at MTs Sheikh Yusuf Gowa - Firdaus Firdaus (PT ARRUS Intelektual Indonesia, 2024)
Indonesian language learning at MTs Sheikh Yusuf is fairly low due to the use of inappropriate learning media which results in students not understanding Indonesian language learning. Isn't it with the existence of various learning media that students are able to have many choices of learning media to use in the learning process according to their personal characteristics. to find out the Effectiveness of Using Toontastic-Based Animated Learning Media on Indonesian Learning Interest of MTs Sheikh Yusuf Gowa Regency Students. The type of research used in this study is a type of quantitative research with an experimental method with a pre experimental method using a one shot case study research design. This shows that the hypothesis test as evidenced by the statistical analysis of the correlation test which states a significant value of 0.040 <0.05. The results of the analysis can also be seen from the value of r count which is 0.371> r table 0.355 so that it can be interpreted that there is a correlation relationship between the use of toontastic-based animated learning media and student learning interest, which means that the use of toontastic-based animated learning media on student learning interest is effective in Indonesian language subjects class VII.A at Madrasah Tsanawiyah Sheikh Yusuf Gowa Regency. The suggestions for future research are expected to make the results of this study a reference for conducting better research by maximising the use of media as a means in the learning process in the classroom.